Data Encoding And Decoding Techniques For NOC Applications (International Journal of Engineering and Computer Science, 2015)
In this paper we present the data encoding and decoding schemes are used to reduce the power dissipation of the communication system in a Network-on-Chip (NoC). In NoC the main source of power dissipation by the network on chip links. The self-switching and coupling-switching activities are caused for link power dissipation. In this paper we present a set of data encoding and decoding schemes are mainly operating at ﬂit level and on an end-to-end basis, which allows us to minimize the both self and coupling switching activities. The self-switching is reduce by checking the switching transition and then the coupling technique is included with the wormhole routed network, that is flits are encoded by the network interface before they are entered in to the network and are decoded  they are focused on reducing hardware.